2022
DOI: 10.1159/000521913
|View full text |Cite
|
Sign up to set email alerts
|

The Global Spread of Severe Obesity in Toddlers, Children, and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Introduction: Severe obesity among children and adolescents has emerged as a public health concern in multiple places around the world. Methods: We searched the Medline database for articles on severe obesity rates in children published between January 1960 and January 2020. For studies with available prevalence rates for an early and a more recent time period, the relative increase in prevalence was imputed. Results: In total, 874 publications were identified, of which 38 contained relevant epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…The disproportionate rates of ID in children and women align with elevated rates of severe obesity in these populations. Severe pediatric obesity rates have escalated since the 1980s [ 19 ], and women with severe obesity (11.5%) currently outnumber men (6.9%) in the United States [ 20 ]. Given the rising levels of obesity in these groups, particularly severe obesity, and its impact on iron metabolism and status, studies that focus on providing how iron biomarkers and ID vary by BMI in large populations could be important for public health education and policy.…”
Section: Introductionmentioning
confidence: 99%
“…The disproportionate rates of ID in children and women align with elevated rates of severe obesity in these populations. Severe pediatric obesity rates have escalated since the 1980s [ 19 ], and women with severe obesity (11.5%) currently outnumber men (6.9%) in the United States [ 20 ]. Given the rising levels of obesity in these groups, particularly severe obesity, and its impact on iron metabolism and status, studies that focus on providing how iron biomarkers and ID vary by BMI in large populations could be important for public health education and policy.…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of severe childhood obesity on health [36] and its rising prevalence in many HICs are alarming [37]. Although emergent scientific evidence is showing that severe obesity is in general associated with lower socioeconomic status [38], more in-depth analyses are needed to study its association with specific SES indicators [39]. Data from the WHO European Childhood Obesity Surveillance Initiative (COSI) found that in European countries, severe obesity was more common among children whose mothers had a lower educational level.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial increase in the rates of severe obesity in children and adolescents has been demonstrated over the past decades, and this phenomenon appears to be nearly universal and not limited to a particular region [ 35 ]. The prevalence of severe obesity among subjects aged 2–19 years in United States, from the years 1971–1974 to the years 2017–2018, raised from 1.0% to 6.1% [ 36 ].…”
Section: Discussionmentioning
confidence: 99%